Pengaruh Tekanan Ketaatan, Kompetensi, dan Pengalaman terhadap Kualitas Audit Judgment (Studi pada BPK RI Perwakilan Provinsi Jawa Tengah) - Devy Ardianti; Herry Laksito (Diponegoro Journal of Accounting, 2016)
The research aims to examine empirically the influence of obedience pressure, competency, and  audit experience on audit judgment quality. In this research, researchers examined the quality of audit judgment in Audit Board of the Republic of Indonesia (BPK) Representative of Central Java Province.The sample was conducted by purposive sampling method. Collecting data was conducted by questionnare distributed directly to auditors as much 100 and only 60 questionnare replayed. This research found statistic result that was significantly positive from obedience pressure influence to audit judgement that was taken by auditor. For competency and audit experience have a positive and significant influence on audit judgment quality. Researchers suggest for future research in order to add more variable and than to extend the population.